Industrial needs towards soft skills among vocational high school pupils in Yogyakarta / Jihan Nabila - Jihan , Nabila (2019)
The vocational high school has a role in producing skilled workers and managing human resources for future labor demand in Indonesia. However, in February 2018, the central bureau of statistics Indonesia reported that Vocational high school graduates rank the highest percentage of unemployment graduates. Several factors caused unemployment, such as lack of soft skill among the student and miss-match of competence between a skill that student learned at school with a skill that required by the industry. Therefore, through this study, the researcher aims to investigate the soft skill that students should learn at school which relevant to industrial needs. The finding of this study can be used as a reference for Vocational High School so that soft skill that taught at school is the same as the soft skill required by the industry. This study adopted a qualitative approach as a research method. The data collection technics are interview, observation, and document analysis. The sample of this research is a vocational high school student, the teacher that teaches a vocational lesson and industry expert. The study conducted in state vocational high school Yogyakarta. The data analyzed using the Saldana Coding Cycle method. This research used NVivo software in the process of data analysis. The result found that there is a set of soft skill that student learns at school which relevant to industrial needs. The set of soft skills divided into personal competence and social competence. Personal competence consists of positive attitude, responsibility, time management, self-management skill, work ethic, grooming. Social competence includes communication, courtesy, interpersonal skill, teamwork, and problem-solving.